Factors influencing the relationship between coaches and athletes with disabilities: a systematic review - Junyan Liu; Hongjun Yu; Adam Bleakney; Yih-Kuen Jan (Frontiers Media S.A., 2024)
IntroductionThe relationship between coaches and athletes with disabilities is critical for enhancing athletes' performance and psychosocial well-being. This study aims to provide evidence-based recommendations for coaches, sports organizations, and policymakers dedicated to supporting athletes with disabilities.MethodsA comprehensive analysis of existing literature was conducted. Five databases were searched, including PubMed, Web of Science, SPORTDiscus, Google Scholar, and China National Knowledge Infrastructure. A total of 22 studies were included for thematic analysis.ResultsThis systematic review identifies key factors influencing the coach-athlete relationship in disabled sports. These factors are categorized into three main domains: professional, interpersonal, and intrapersonal. In the professional domain, effective coaching requires sport-specific skills and adaptive techniques tailored to the unique needs of athletes with disabilities. Coaches must understand the technical and tactical aspects of each parasport and adapt training plans to optimize performance and foster independence. The interpersonal domain emphasizes communication strategies and team-building practices. Effective communication involves understanding athletes' needs and adapting approaches to maximize strengths. Building rapport, managing conflict, and fostering a supportive team environment are crucial for maintaining a positive coach-athlete relationship. The intrapersonal domain highlights the importance of self-reflection and continuous learning. Coaches who engage in self-reflection and professional development better understand their behaviors and biases, enabling them to tailor coaching strategies to the specific needs of athletes with disabilities. Continuous learning is essential for remaining responsive to the evolving needs of these athletes.DiscussionThis review underscores the importance of a holistic approach that integrates professional expertise, interpersonal skills, and intrapersonal awareness. By addressing these factors, it provides a foundation for developing more effective coaching strategies and supports for athletes with disabilities, ultimately enhancing their performance and well-being. Future research should explore cultural differences, the specific coaching needs of athletes with intellectual disabilities, and the impact of policies and structural barriers on the coach-athlete relationship in disabled sports.